EFFECT OF IRRIGATION NEEDLE DESIGN ON CALCIUM HYDROXIDE REMOVAL: AN IN VITRO SCANNING ELECTRON MICROSCOPY STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effect of irrigation needle design on of calcium hydroxide removal from root canals using scanning electron microscopy.Methods: 36 extracted single-rooted human premolars were instrumented and medicated with calcium hydroxide for seven days. Specimens were randomly allocated into two groups (n = 18): side-port needle (CanalPro Side-Port Tips) and flexible needle (IrriFlex). After a standardized irrigation protocol, roots were longitudinally split and examined under scanning electron microscopy at the coronal, middle, and apical thirds. Residual calcium hydroxide was scored using the Kuga scale (0-3). Data were analyzed using Mann-Whitney U and Friedman tests, followed by Wilcoxon signed-rank tests with Bonferroni correction (α = 0.05).Results: In both groups, higher residual scores were observed in the apical third compared with the coronal and middle thirds. No significant differences between needle designs were detected at the coronal or middle levels (p > 0.05). However, at the apical third, the flexible needle showed significantly lower residual scores (p = 0.040).Conclusion: A flexible irrigation needle design may enhance calcium hydroxide removal at the apical third when assessed by scanning electron microscopy.
Keywords: Calcium hydroxide, irrigation needle, IrriFlex, scanning electron microscopy (SEM).